Rapid Progressive Glioblastoma despite Radiation in a Patient with Myelodysplastic Syndrome - Eric T. Wong; Justin Moore; Lauren Hertan; Erik J. Uhlmann (Case Reports in Oncology, 2021)
The rapidity of glioblastoma progression can be exacerbated by impaired systemic immune surveillance. We describe an elderly woman with advanced 5q– myelodysplastic syndrome (MDS) associated with trilineage dysfunction in hematopoiesis. She also developed multiple solid tumor malignancies including ER/PR-positive and HER2-negative breast cancer, probable lung cancer without histologic confirmation, and primary glioblastoma with a high proliferation index of 80%. Because of low platelet counts of 20,000–30,000/µL that required periodic transfusion and a reduced white cell count of 600–900/µL, she was deemed unsafe to take concomitant daily temozolomide during radiation and her glioblastoma was treated with a shortened course of radiotherapy alone. Her baseline absolute neutrophil count was 110–390/µL, and CD4+ and CD8+ lymphocyte counts were 235/µL and 113/µL, respectively. During the last week of radiation, the patient developed a nonfluent aphasia, increased fatigue, and aspiration pneumonia. A gadolinium-enhanced head MRI, obtained 2 days after completion of radiation and 39 days after biopsy, demonstrated near tripling of the size of the left frontal tumor with a significant amount of adjacent cerebral edema. This case raises the possibility that advanced MDS is a negative immunomodulatory condition that can accelerate glioblastoma progression.